PELATIHAN PRAKTEK DISTRIBUSI MENINGKATKAN KELINCAHAN MENGGIRING SEPAK BOLA DITINJAU DARI KEMAMPUAN MOTOR EDUCABILITY PADA MAHASISWA SEMESTER II PROGRAM STUDI PJKR UNIV.PGRI-NTT - Runesi, Salmon; Sutjana, I Dewa Putu; Boleng, Lukas M. (Sport and Fitness Journal, 2015)
This study aims to determine the distribution practice training raise the agility in dribbling ball viewed from motor educability skills.The study was conducted with pretestposttest group design in the second semester students Program Study of PJKR PGRI University- NTT, with a number of samples 28 people who were divided into two groups and each group totaled 14 people. Both groups were equally practical training distribution with high and low motor educability abilities, conducted for 8 weeks with a frequency of exercise 3 times per week. The results were analyzed descriptively to variants age, height, weight, body mass index and the motor educability in both groups whose data were taken before the determination and implementation of training samples. Normality test is using the Shapiro-Wilk test and homogeneity test with Leven's test. T-paired test is to know different of agility time cost for dribbling of group 1 (high motor educability) with the average before training is 15.217±0.496 seconds, and the average after training is 10.719±0.470 seconds with difference = 4.497 and the increasing of percentage is 29.52% (p<0.05). While at group 2 (low motor educability) low educability motor group with a mean 15.746±0.662 seconds, and the average after training 12.105±0.565 seconds with the different = 3.640 seconds and increasing of percentage 23.12% (p <0.05). Results of the different effect of changes in time cost dribble soccer agility was tested with t-independent between groups before and after training on the significance limit of ? = 0.05. The average of time changing before training with p?0.05, it means the early condition is equal and after training has value p<0.05.These results indicated that the high motor educability group and low educability motors are equally give effect to an agility increase (p <0.05). However, the increasing of high motor educability is better than the low motor educability. Suggested further intensified at high motor educability skills in the training process, athlete recruitment and implementation of motion activity, because it gives the increasing effect.
Keywords: Agility, Dribbling ball, Distributionexercise, The motoreducability.